Gagasan Konsentrasi Pembidangan Jurusan Pendidikan Agama Islam Fakultas Tarbiyah (By Using Separated-Subject Matter Curriculum Approach) Ahmad Muthohar - Ahamad Muthohar (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: In general, curriculum materials in the fields of PAI includes four categories, namely 1) the materials associated with the al- Quran and al-Hadith, 2) materials relating to faith and morality, 3) material related to fiqh, and 4) materials relating to the history of Islam. The fact shows that the various departments and institutions is not specified into the fields. This paper will outline the concept of specified in PAI Department in accordance with the approach to the majors Separated-Subject Matter Curriculum planning which will result in five divisions material into five PAI study program, those are program of study: 1) Islamic Education (PAI), which prepare students to become a teacher of Islamic religion in school, 2) The course of study the Quran, Hadith, 3) The course of study Aqidah Akhlaq, 4) Fiqh Study Program, and 5) Program Cultural History of Islamic studies which prepare the students to be a teacher at the madrasah. Keywords : Division Concentration, Islamic Religious Education, Separated-Subject Matter Curriculum Approach.